Search strategy for scientific information applied to the return to work of people with disabilities - Galarza-Iglesias, Ana Milena (Universidad y Salud, 2020)
Introduction: The professionals to exercise their practice in an updated and effective way in the matter of return to work of persons with disabilities must support their actions in the scientific evidence. With technology you have access to a lot of information. To be effective and retrieve the data that is required the use of search strategies. Objective: To demonstrate the relevance of a search strategy to recover scientific publications, in this case, labor reimbursement of persons with disabilities. Materials and methods: The search strategy is systematically presented based on the definition of the question, identification of search terms in common and controlled language, search equation, search-retrieval of articles, inclusion-exclusion criteria, selection of articles, critical reading and answer to research question. The above can be reproduced by adjusting descriptors according to professional interest. Results: 15 articles were retrieved that answer the example question evidencing the relevance of the search strategy. Conclusions: An academic information search strategy allows retrieving articles that are relevant for the researcher and professionals in their daily practice.